Identification Of The Role Of Bamboo Plants As Riverbank Protection: A Case Study In The Krueng Meuh Watershed - Nuraida; Siti Hajar; Sayed Ahmad Zaki Yamani; Reza Fahmi; Desyan Ria; Aiya Sofia (Journal of Synergy Landscape, 2025)
The problem of riverbank degradation due to erosion and landslides is an important problem in river basin management, especially in the Krueng Meuh Sub-watershed. Bamboo plants have a strong root system and a dense clump structure, so they have great potential in soil and air conservation on riverbanks. This study aims to identify the types of bamboo that grow on riverbanks and analyze their role in riverbank conservation in the Krueng Meuh Sub-watershed. This study is a descriptive exploratory study by exploring the riverbank along 50 meters from the left and right banks of the river. The methods used include direct observation of bamboo morphology, collection of plant characteristic data, and assessment of conservation potential based on clump density and root system strength. The results of the study found five types of bamboo in the Krueng Meuh Sub-watershed, namely Duri Bamboo (Bambusa bluemeana), Talang Bamboo (Schizostachyum Brachcladum), Betung Bamboo (Dendrocalamus asper), Ampel Bamboo (Bambusa vulgaris), and Regen Bamboo (Gigantochloa pruriens). Each species has different morphological characteristics and root systems, and contributes to the stability of riverbanks. The bamboo species with the highest potential in protecting riverbanks are Dendrocalamus asper and Schizostachyum Brachcladum based on root strength and clump density. In conclusion, betung bamboo and talang bamboo have the highest effectiveness in protecting riverbanks due to their deep roots and dense clump structure. Riverbank vegetation management by considering local bamboo species can be an effective and sustainable conservation strategy.